Gestão de meios hospedagem durante a pandemia do Covid-19: aplicação de um protocolo de biossegurança na cidade de Jaguarão/RS - (:unkn) unknown (Universidade Federal do Pampa, 2020)
The present work addresses the Covid-19 Pandemic and management of the Means of Lodging in this pandemic period, having as the main objective of the work to elaborate a proposal of biosafety protocol for the means of lodging of the municipality of Jaguarão/RS, thus enabling contagion by Covid-19 to be minimized. The specific objectives of the project are: to reduce covid-19 contagion between guests and employees; propose a biosafety protocol according to the guidelines proposed by who; strengthen the relationship between the Unipampa Tourism Course, Jaguarão campus and the means of lodging of the municipality of Jaguarão/ RS; and finally, contribute to make guests feel safe in staying in the means of lodging Jaguarão, and thus minimize the negative effects of the crisis in the establishments. In the course of the research, it is perceived that the city has a structure of tourist services in the field of hospitality for Tourism, however, with the arrival of Covid-19, everything has changed and the enterprises have been negatively impacted by the reduction of guests. The methodology used in this project was established regarding the qualitative approach and the applied nature, using the methodological procedures of the bibliographic review, exploratory research, and interview in the virtual format. The interviews were conducted in November 2020, considering an already advanced period of managers in their experience with the limitations imposed by the pandemic. With this present project, it is perceived that the elaboration of the biosafety protocol, even will contribute not only to make guests and employees feel safe in relation to the means of lodging of the city, but will also help to contain the spread of the disease by the municipality of Jaguarão.
Keywords: Turismo; Meios de Hospedagem; Covid-19; Protocolo de Biossegurança; Jaguarão, RS; Tourism; Means of Lodging; Covid-19; Biosafety Protocol; Jaguarão, RS; CNPQ::CIENCIAS SOCIAIS APLICADAS